(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Andrographolide, the major bioactive compound responsible for most pharmacological activities such as anticancer, antimicrobial activity exhibited by the Andrographis paniculata plant is present in small quantities. In addition, the genus Andrographis has about 28 species most of which possess no medicinal value. The deoxyribonucleic acid (DNA) barcode is utilized in species identification and plant authentication. Objectives: This study aimed at authenticating Andrographis paniculata using DNA barcodes and improving the yield of andrographolide via enzymatic treatment. Materials and Method: The DNA of Andrographis plant was obtained using the Qiagen kit. The psbA-trnH and rbcL DNA barcode regions were amplified using polymerase chain reaction (PCR). Presence of amplified regions was confirmed using gel electrophoresis and the amplicons were sequenced. A blast N search was performed on the sequenced DNA. The constituents of A. paniculata dried leaves was extracted using methanol, followed by treatment with and without β glucosidase. The extract obtained was dried and partitioned using ethyl acetate. The ethyl acetate fraction was concentrated and dissolved in methanol. Andrographolide content was determined using high performance liquid chromatography (HPLC). Results: The psbA-trnH and rbcL DNA regions were successfully amplified having 358 and 604 bp respectively. The DNA barcode sequences obtained were identical to the psbA-trnH (97%) and rbcL (99%) genes of A. paniculata voucher MICET P00101. The mean andrographolide yield was 9.4±0.11mg/g and 8.9±0.13mg/g dry weight for the treatment and control groups respectively; statistical analysis at p = 0.05 shows a significant difference. Conclusion: The Andrographis plant used in this study was confirmed to be Andrographis paniculata, enzymatic treatment increased andrographolide yield from the plant.